If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2xy + 3y + -3x + -1 = 0 Reorder the terms: -1 + -3x + 2xy + 3y = 0 Solving -1 + -3x + 2xy + 3y = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '1' to each side of the equation. -1 + -3x + 2xy + 1 + 3y = 0 + 1 Reorder the terms: -1 + 1 + -3x + 2xy + 3y = 0 + 1 Combine like terms: -1 + 1 = 0 0 + -3x + 2xy + 3y = 0 + 1 -3x + 2xy + 3y = 0 + 1 Combine like terms: 0 + 1 = 1 -3x + 2xy + 3y = 1 Add '-3y' to each side of the equation. -3x + 2xy + 3y + -3y = 1 + -3y Combine like terms: 3y + -3y = 0 -3x + 2xy + 0 = 1 + -3y -3x + 2xy = 1 + -3y Reorder the terms: -1 + -3x + 2xy + 3y = 1 + -3y + -1 + 3y Reorder the terms: -1 + -3x + 2xy + 3y = 1 + -1 + -3y + 3y Combine like terms: 1 + -1 = 0 -1 + -3x + 2xy + 3y = 0 + -3y + 3y -1 + -3x + 2xy + 3y = -3y + 3y Combine like terms: -3y + 3y = 0 -1 + -3x + 2xy + 3y = 0 The solution to this equation could not be determined.
| h(x)=40t-5t^2 | | s=40t-5t^2 | | 36x^4-72x^3+37x^2-2x+1=0 | | 5x-9=16-3x | | (3x)/5x_2=-4 | | (3*9.14+4)+(2+9.14-5)*2=58 | | -20=15-7x | | (6y-5)/2y=7/9 | | 9(2n-7)=27 | | 4(12+4r)=2(10r+8) | | (3x+4)+(2x-5)*2=58 | | (8x-3)/3x=-2 | | ln5/25 | | 3x*5x+2=-4 | | 2(3n+6)=2(n-8) | | 0.5x-2=-x+12 | | -2(12a+12)=-10a-2(1+7a) | | 2x-x-1/4-1/5-1=0 | | -6p-14=4p+6 | | -9-6-4v-3=1+5v+8 | | -x+3x=6-x | | -8k+7j=12k-3j | | 10-4t=30 | | 8x-3/3x=-2 | | 2x-1/4-x-1/5=1 | | x^2+2sqrt(3x)+3=0 | | 5,8=12/x | | X*x=3x+2 | | 4,7=12/x | | (5x+20)+(3x+76)+(x+196)=180 | | 5y+6-(-3+4y)=10 | | x-5^2-x-3^5=1/2 |